2010
DOI: 10.3310/hta14530
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of screening high-risk HIV-positive men who have sex with men (MSM) and HIV-positive women for anal cancer.

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 28 publications
1
37
0
2
Order By: Relevance
“…An early cost-effectiveness study from the United States had suggested that biennial screening using cytology to screen MSM would be associated with an incremental cost-effectiveness ratio of $13 000 per quality adjusted life years saved [16]. A costeffectiveness analysis from the United Kingdom published in 2010 concluded that many of the criteria for assessing the need for a screening programme for HIV-positive MSM were not met [17], and the authors concluded that it was unlikely that screening for anal cancer would be cost effective. In a more recent Canadian study of 400 HIV-positive MSM, using a decision analytical model, the investigators concluded that despite higher unit costs, the limitations of both HPV testing and cytology meant that anoscopy would be the most cost effective strategy [18].…”
Section: Discussionmentioning
confidence: 99%
“…An early cost-effectiveness study from the United States had suggested that biennial screening using cytology to screen MSM would be associated with an incremental cost-effectiveness ratio of $13 000 per quality adjusted life years saved [16]. A costeffectiveness analysis from the United Kingdom published in 2010 concluded that many of the criteria for assessing the need for a screening programme for HIV-positive MSM were not met [17], and the authors concluded that it was unlikely that screening for anal cancer would be cost effective. In a more recent Canadian study of 400 HIV-positive MSM, using a decision analytical model, the investigators concluded that despite higher unit costs, the limitations of both HPV testing and cytology meant that anoscopy would be the most cost effective strategy [18].…”
Section: Discussionmentioning
confidence: 99%
“…The baseline prevalence of HPV16/18, LGAIN, and HGAIN and incidence of HPV types 16 and 18 in HIV-negative MSM were based on a meta-analysis [2]. The natural history parameters for disease progression and regression were based on a cost-effectiveness analysis by Czoski-Murray et al [12], who derived these estimates from two large prospective cohort studies [13, 14]. Data from Tong et al [15] were used to estimate HGAIN regression.…”
Section: Methodsmentioning
confidence: 99%
“…Health-related utilities (defined as preference-based valuation of the health states) for HGAIN, anal cancer, and HIVpositive status (based on CD4 cell count) were obtained from a cost-effectiveness analysis published elsewhere [25] (see Supplementary Appendix Table T1.4). We further adjusted all health-related utilities by age [26].…”
Section: Health-related Utilitiesmentioning
confidence: 99%